The Dopamine Agonist Bromocriptine Differentially Affects Fronto-Striatal Functional Connectivity During Working Memory - Wallace, Deanna L.; Vytlacil, Jason J.; Nomura, Emi M.; Gibbs, Sasha E.; D'Esposito, Mark (Frontiers in Human Neuroscience, 2011)
We investigated the effect of bromocriptine, a dopamine agonist, on individual differences in behavior as well as frontal-striatal connectivity during a working memory task. After dopaminergic augmentation, frontal-striatal connectivity in low working memory capacity individuals increases, corresponding with behavioral improvement whereas decreases in connectivity in high working memory capacity individuals are associated with poorer behavioral performance. These findings corroborate an inverted U-shape response of dopamine function in behavioral performance and provide insight on the corresponding neural mechanisms.